The Effect of Green Color Therapy on Lowering Blood Pressure in the Elderly with Hypertension - A. Karim, Masni; Syamsuddin, Fadli; Pakaya, Abdul Wahab (Bantayang Omni Cendekia, 2024)
Background: Hypertension is one of the dangerous diseases because it is one of the main risk factors that lead to cardiovascular disease, Hypertension can be overcome by giving non-pharmacological actions, namely green color therapy that can lower blood pressure Objective: The purpose of this study was to determine the effect of green color therapy on reducing blood pressure in the elderly Methods: This type of research is a study using Quasy experimental sampling using purposive sampling with a total of 24 respondents Results: The data obtained in this study were processed using the paired T-test method on the control group obtained a p value of 0.674 (α>0.05) while in the intervention group a p value of 0.001 (α<0.05) was obtained Conclusion: The conclusion of this study means that there is a significant effect of green color therapy on reducing blood pressure in the elderly with hypertension. So it is necessary to give green color therapy to the elderly who have hypertension to lower blood pressure